2017
DOI: 10.1016/j.devcel.2017.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Dependent Endothelial YAP Regulation Contributes to Vessel Maintenance

Abstract: Endothelial cells (ECs) line the inside of blood vessels and respond to mechanical cues generated by blood flow. Mechanical stimuli regulate the localization of YAP by reorganizing the actin cytoskeleton. Here we demonstrate blood-flow-mediated regulation of endothelial YAP in vivo. We indirectly monitored transcriptional activity of Yap1 (zebrafish YAP) and its spatiotemporal localization in living zebrafish and found that Yap1 entered the nucleus and promoted transcription in response to blood flow. In cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
253
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(270 citation statements)
references
References 59 publications
16
253
1
Order By: Relevance
“…(B) The ox-LDL-treated group had significantly higher miR-496 expression as compared to the control group; ÃÃ P < 0.01 versus PBS; n ¼ 3. Furthermore, they found that adjusting the blood flow to induce nuclear YAP1 translocation in vascular endothelial cells could regulate the expression of filamentous actin and angiomotin, thereby inducing the expression of auxiliary transcription factors (Nakajima et al, 2017). (D) Luciferase reporter assays suggesting that WT miR-496 overexpression in NIH-3T3 cells significantly inhibited the activity of luciferase carrying the Yap1 3 0 UTR sequence.…”
Section: Discussionmentioning
confidence: 99%
“…(B) The ox-LDL-treated group had significantly higher miR-496 expression as compared to the control group; ÃÃ P < 0.01 versus PBS; n ¼ 3. Furthermore, they found that adjusting the blood flow to induce nuclear YAP1 translocation in vascular endothelial cells could regulate the expression of filamentous actin and angiomotin, thereby inducing the expression of auxiliary transcription factors (Nakajima et al, 2017). (D) Luciferase reporter assays suggesting that WT miR-496 overexpression in NIH-3T3 cells significantly inhibited the activity of luciferase carrying the Yap1 3 0 UTR sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells are elusive targets for chemotherapy due to the heterogeneity and genetic instability. However, ECs are genetically stable and have a low mutational rate . The homogeneity, genetic stability, and low mutational rate of ECs provide a low toxicity treatment option without the induction of resistance .…”
Section: Angiogenesis and Antiangiogenesismentioning
confidence: 99%
“…However, ECs are genetically stable and have a low mutational rate. 35 The homogeneity, genetic stability, and low mutational rate of ECs provide a low toxicity treatment option without the induction of resistance. 36 Antiangiogenic agents are considered an ideal treatment of cancers by some and have been investigated both as monotherapies and in combination with traditional drugs.…”
Section: Antiangiogenic Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…YAP can be localized in the cytoplasm or translocated to the nucleus, where it associates with TEAD transcription factors 7. Previous studies have shown that various forms of mechanical stimulation, such as substrate stiffness, strain, and shear stress, affected YAP localization by actin fiber remodeling 6, 8, 9, 10. YAP was shown to be involved in the effect of shear stress on ECs and blood vessels,10 however its role in the effect of mechanical strain on vascularization is yet to be established.…”
Section: Introductionmentioning
confidence: 99%